2009
DOI: 10.1080/10717540802666980
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of copolymers of methylmethacrylate and 2-hydroxyethyl methacrylate for the aqueous solubilization of Paclitaxel

Abstract: The aim of the present work is the modification of a hydrophobic polymeric macromolecule, polymethylmethacrylate, by introducing hydrophilic moieties of 2-hydroxyethyl methacrylate within the polymer chain. Synthesis, characterization, and drug delivery control capabilities exerted on a highly hydrophobic drug (Paclitaxel) are illustrated. In particular, the dependency of the drug delivery kinetic on the fraction of hydrophilic units inserted in the copolymer chain was studied. Results showed that it is possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Weight losses corresponding to first and second decomposition temperatures correlated well with PHEMA and PMMA fractions, respectively ( Figure ), as determined from proton NMR analysis (Table ). These data agreed well with the literature . After synthesizing the copolymers, CP1 and CP2 were used to encapsulate paraffin wax (25 wt% (w/w)) to fabricate PCM entrapped microparticles using a simple one‐step oil/water emulsion solvent evaporation technique ( Scheme ).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Weight losses corresponding to first and second decomposition temperatures correlated well with PHEMA and PMMA fractions, respectively ( Figure ), as determined from proton NMR analysis (Table ). These data agreed well with the literature . After synthesizing the copolymers, CP1 and CP2 were used to encapsulate paraffin wax (25 wt% (w/w)) to fabricate PCM entrapped microparticles using a simple one‐step oil/water emulsion solvent evaporation technique ( Scheme ).…”
Section: Resultssupporting
confidence: 86%
“…Tg was found to decrease with the increase of PHEMA content ( Figure ) (Table ). This might be due to the formation of random copolymer of MMA and HEMA reducing the H‐bonding of HEMA unit that may lead to enhanced chain flexibility . The copolymer compositions can also be estimated from thermogravimetric analysis which provided the information about weight loss of individual polymers at two different degradation temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings clearly demonstrated the formation of amide linkages. The remaining peaks were assigned as follows: a CH stretching at 2970 cm −1 , an NH deformation at 1440 cm −1 , a COC or OH bending at 1393 cm −1 ,, a COC at 1277 cm −1 , a CC at 1233 cm −1 , a CNH at 1115 cm −1 , a CN stretching at 1042 cm −1 ,, a COOC at 1020 cm −1 , a CH out of plane bending vibration of the aromatic ring at 874 cm −1 , an NH wagging at 813 cm −1 and a CC bending at 602 cm −1 . These findings indicated that MAVA was modified by NA by an amidation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, side-effects due to the toxicity towards healthy tissues limit the administration doses, compromising the effectiveness of the treatment (Van Zuylen et al, 2001). The common practice to incorporate hydrophobic and poor water-soluble drugs within biocompatible materials has been shown to significantly reduce systemic toxicity and in the meanwhile to increase the drug solubility (Torchilin, 2004;Liu et al, 2006;Nishiyama & Kataoka, 2006;Silvestri et al, 2009a). Novel drug delivery systems are currently studied and developed to optimize drug release profiles with the aim to be employed in different therapeutic areas.…”
Section: Introductionmentioning
confidence: 99%